Solution of Fuzzy Differential Equation (Journal of the College of Basic Education, 2025)
This study addresses fuzzy initial value problems (FIVPs) to define initial conditions. We present numerical solutions for fuzzy differential equations using a modified two-step Simpson method and Runge-Kutta algorithms of orders 2–6, including convergence analysis. Computer programs generate approximate solutions, and we compare the performance of all methods through numerical examples.